Fumonisin mycotoxins: the effect of digestion on the different forms. Toxic effects and biological detoxification: Review - Varga-Szatmári, Viktória; Vargáné Visi, Éva (Acta Agraria Kaposváriensis, 2024)
Mycotoxin contamination can occur at almost all levels of food production, processing, storage and distribution, and causes significant economic damage in animal husbandry, animal and crop production. Ingestion of foodborne mycotoxins can cause numerous diseases and health impairments. This review presents the different forms of fumonisin that can occur in foods and feeds, as well as the possible effects of digestion on these forms. The description of the toxicity of fumonisins includes the biochemical background, the different degree of toxicity of individual fumonisin metabolites, and the caused detrimental health effects on different species. The biological detoxification of mycotoxins has an advantage over physical and chemical methods with respect to nutrient losses, therefore this review focuses on the biological processes that can lead to the elimination of fumonisins. The presented methods involve bacterial binding and degradation that can promote the detoxification of fumonisins consumed with food or feed.
Keywords: fumonisin; gastrointestinal tract; food matrix; digestion; bioaccessibility